Factors affecting the use of antioxidant supplements in patients with late AMD - Yu, Alice L.; Paul, Tobias; Schaumberger, Markus; Welge-Lüssen, Ulrich-Christoph (Clinical Ophthalmology, 2014)
The purpose of this study was to assess the use of oral antioxidant supplements in patients with late age-related macular degeneration (AMD) and to identify influencing factors that may affect the use of such supplements.The study included 47 patients with late AMD. Using a questionnaire, the patients were asked for their demographic, ophthalmologic, and systemic data, their source of recommendation of antioxidant use for AMD, and/or their reasons for nonuse. The demographic, ophthalmologic, and systemic information was correlated with use or nonuse of oral antioxidant supplements for AMD.Sixty-eight percent (32/47) of patients took antioxidant supplements for AMD and 32% (15/47) of patients did not. There were no statistically significant differences in demographic, ophthalmologic, and systemic parameters between patients with late AMD who used supplements and those who did not. Two thirds of patients with late AMD (66%, 31/47) reported being recommended oral antioxidant supplements for AMD by their ophthalmologist. Patients who did not use antioxidant supplements either did not obtain any recommendation or did not believe in their benefits.This study shows that most patients with late AMD use antioxidant supplements despite the recommendation to do so being missing in the Age-Related Eye Disease Study. Our study emphasizes the importance of seeking further therapeutic options for patients with late AMD.
EVALuna2:21199